Personality in Zoo-Hatched Blanding’s Turtles Affects Behavior and Survival After Reintroduction Into the Wild - Allard, Stephanie; Fuller, Grace; Torgerson-White, Lauri; Starking, Melissa D.; Yoder-Nowak, Teresa (Frontiers in Psychology, 2019)
Reintroduction programs in which captive-bred or reared animals are released into natural habitats are considered a key approach for conservation; however, success rates have generally been low. Accounting for factors that enable individual animals to have a greater chance of survival can not only improve overall conservation outcomes but can also impact the welfare of the individual animals involved. One such factor may be individual personality, and personality research is a growing field. This type of research presents animal welfare scientists with the opportunity to develop behavior profiles that may predict how particular individuals cope with challenges. This has direct implications for both in situ and ex situ populations and can bridge the gap between animal welfare and conservation. We designed a project to ascertain the presence of personality traits in Blanding’s turtles (Emydoidea blandingii), a species of special concern in the state of Michigan, and assess potential links between traits and post-release success. As hypothesized, the Blanding’s turtles in this study displayed behavioral responses to modified open field tests indicative of distinct personality traits: exploration, boldness and aggression. Additionally, the personality traits were correlated differently with survival and behavior patterns when the turtles were released into the Shiawassee National Wildlife Refuge. More exploratory turtles had higher survival rates, while neither boldness nor aggression were related to survival. Exploratory turtles were also more likely to travel longer distances after release. The use of muskrat dens was related to increased survival, and both bolder and more exploratory turtles made higher use of this feature. Exploratory and aggressive turtles were found basking outside of water more often, while bold turtles were more likely to be found at the water surface. Both of these basking behaviors may increase the risk of predation and may be reflective of a trade-off between risk and behaviors related to physiological health. Understanding how personality affects behavior and survival post-release can be a critical tool for improving reintroduction success. Zoo animal welfare scientists and practitioners can implement approaches that improve the welfare of individuals within the context of conservation initiatives.